On the Contributions of the Northeast Cold Vortex to the Formation and Evolution of Backflow Blizzard - Yan, Qi; Cui, Jin; Tan, Zhenghua; He, Bao-Jie (Frontiers in Earth Science, 2022)
Blizzard is a severe weather-related disaster with significant environmental, economic, and social impacts. What is worse, the blizzard is increasingly frequent along with climate change. To enhance resilience, it is important to accurately estimate the blizzards. While some studies have reported the blizzard formation and characteristics, limited studies have not well presented the backflow blizzard associated with the cold vortex in Northeast China. In order to overcome this research gap, this study aims to analyze the characteristics of a backflow blizzard in Liaoning, China, and reveal the reasons behind the spatial heterogeneity of snowstorm intensity and duration. With observation data and mesoscale numerical simulation, this study discovered that the northeast cold vortex was the combined results of airflows from the Sea of Japan transported by the easterly airflow, the East China Sea, and the Yellow Sea transported by the southeast airflow, and the low-level southwest airflow, and the vortex was an important driver to the blizzard. Results further indicate that the interactions of airflow movement, water vapor variation, and frontogenesis occurrence at different layers caused the differences in snowfall intensity, duration, and volume at Zhangwu and Huanren stations. In particular, at Zhangwu station, there was an interaction of warm-wet and cold-dry airflows, but low-layer water vapor content was small, under which background only the cold air pushed the warm air as the southwest wind did not increase significantly, leading warm-humid air to be forced to climb and resulting in frontogenesis at 700–925 hPa. Therefore, the situation of no frontogenesis and poor humidity conditions in the low-level cold air contributed to the weak and a short-duration of snowfall at Zhangwu Station. The water vapor content of warm-wet and cold-wet airflows over Huanren station was better than that at Zhangwu so that during cold and warm air interaction, there was frontogenesis at 500–925 hPa. Near the top of the inverted trough in the ground layer, there was a convergence of the southeasterly wind and the northeasterly winds, resulting in the occurrence of horizontal frontogenesis throughout the layer of 500 hPa and forming an upward movement column. Moreover, a deep near-saturated water vapor layer formed below 600 hPa due to the upward movement column. Overall, the abundant water vapor combined with the deep dynamic uplift led to the heavy and long duration of snowfall at the Huanren station. Overall, this study is an important reference for understanding the backflow blizzard and its mechanism. Moreover, it is conducive to the accurate estimation of backflow blizzards in Northeast China and eastern China, the eastern coast of the Korean peninsula, and other similar areas where on the east part of the continent is the ocean.